Modernism on the Fringe: Spain’s Far-Right Avant-Garde - Anderson Araujo (Ex-centric Narratives: Journal of Anglophone Literature, Culture and Media, 2023)
Spanish modernist writers on the left of the political spectrum, such as Lorca, Unamuno, and Rafael Alberti, have garnered much critical attention in Anglophone scholarship. In contrast, their peers who embraced parafascist Nationalism and Falangism in the 1920s and 1930s have been largely overlooked. This paper sheds light on three prominent authors on the ultraconservative vanguard, who are nevertheless virtually unknown outside of Spain: Ernesto Giménez Caballero, Ramiro Ledesma Ramos, and José María Pemán. Despite their controversial politics, they significantly influenced the country’s cultural and intellectual history. The study underscores the impact of Falangist and Fascist ideologies on modernist production in Spain during the Second Republic and its aftermath. Unlike politically radical avant-garde movements like Futurism, Spanish right-wing modernism lacked international recognition, adopting an insular aesthetic that glorified the nation’s imperial past and conservative Catholicism. Aligned with the Franco dictatorship, the movement underwent a transformative phase during the Spanish Civil War, shaping the ethnonationalist concerns of these writers. As the historiography of modernism evolves, the paper advocates acknowledging Spain’s far-right avant-garde as a significant cultural force, challenging the prevailing Anglocentric perspective on modernism’s development.